Knowledge, application and integration of ICT - CT and PET by university yeachers in the city of Ambato (Docentes 2.0 Journal, 2020)
Technology is not something of recent times, it has become the engine that moves the development of knowledge from the origins of man, the accelerated development of these, has generated transformations within the educational environment, playing a primary role in the teaching processes - learning Under this context, this research aims to: Determine the level of knowledge, application and integration of ICT / CT / PET by university teachers in the city of Ambato. The methodological design of this research is mixed with a descriptive - cross-sectional study through the qualitative - quantitative perspective. The study population represented 250 university teachers from the city of Ambato. For the analysis, criteria established based on guidelines of the ICT Competencies Pentagon (MEN, 2013) were considered, where the five competencies that the teacher should develop at the ICT / CT / PET levels are presented: Technological, Pedagogical, Communicative, Management and Research Among the main findings, it is determined that university teachers have an average level of knowledge of ICT (96%), TAC (55%) and PET (26%); ICT application (77%), TAC (28%) and PET (13%); and, of ICT intervention (68%), TAC (15%) and PET (6%).
Keywords: TIC; TAC; TEP; university teacher